The impact of digital transformation on corporate total factor productivity - Li, Na; Wang, Xiaohong; Wang, Zeren; Luan, Xiangyu (Frontiers in Psychology, 2022)
Corporates need to break through the dilemma of system and efficiency with the help of digital transformation in the digital economy era. This paper aims to examine the influence of digital transformation on corporate total factor productivity by investigating whether and how corporate technical cooperation and ESG performance mediate and moderate the relationship between them. We find that digital transformation increases corporate total factor productivity using a panel dataset of Chinese manufacturing listed firms between 2016 and 2020. Moreover, we show that this positive impact is more pronounced when corporates have higher ESG performance. And corporate technical cooperation plays a mediating role between digital transformation and corporate total factor productivity. ESG performance also plays a positive moderating role in the relationship between digital transformation and corporate technical cooperation. Our results contribute to the literature on digital transformation and corporate total factor productivity at the micro-corporate level. Further, our findings offer insights to decision-makers and regulatory bodies regarding the current practices of digital transformation and its potential economic impact.